Management and survival rates for malignant pleural effusions at Tishreen University Hospital - محمد الخير; فراس حسين; شريف عثمان (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: Malignant pleural effusion is defined as an effusion containing neoplastic cells. It is most common in metastatic tumors and it causes dyspnea, cough and chest pain. Prognosis varies depending on the location and stage of the primary tumor, the patient’s clinical condition, age, and other factors. As a result of this difference and because of the large number of malignancies leading to malignant effusions; it is difficult to predict the prognosis or survival rates of these patients. Therefore, following them in terms of these rates and their correlation with aforementioned factors enables us to draw results that serve future research related to diagnostic and therapeutic methods and warning of this group. Research methods: We conducted a study on patients with malignant and semi-malignant pleural effusions in Tishreen University Hospital between the beginning of January and the end of June of 2020, and then followed them up for a whole year. The patients’ gender, age, the type of the primary tumor and its histological pattern were recorded. Patients were also classified according to whether they had undergone thoracentesis or pleural biopsy, the results of the cytological study of the pleural fluid when it was performed, the side of the effusion and finally whether patients undergone pleurodesis or didn’t. The survival time was calculated from the diagnosis of pleural effusion until death or the passing of a year; whichever happened first. The final patient population was 89. Results: Male patients predominated our study group, and so did the patients that are younger than 60 years. Lung tumors were the most common cause of effusion (28.1%), followed by hematological tumors and metastases of unknown origin. Histologically, adenocarcinoma occupied the largest percentage (28.1%), followed by non-Hodgkin’s lymphoma and squamous cell carcinoma. Finally, pleurodesis was performed in 23.6% of the sample. Survival rates did not differ significantly between males and females, nor between the two age groups. None of the primary tumors was associated with a significant effect on survival rates. The effect of adenocarcinoma on survival rates was statistically (P < 0.001) and clinically significant; greatly reducing these rates. Finally, pleurodesis was a statistically significant factor (P = 0.04) in improving survival rates. Conclusions: Malignant pleural effusion is associated with low survival rates. Lung tumors are the most common cause of this effusion. Adenocarcinoma is the most common histological pattern, and it is of great statistical importance in reducing the survival rates of patients with malignant pleural effusion. Finally, pleurodesis was associated with significantly better survival rates.